2011
DOI: 10.1159/000330708
|View full text |Cite
|
Sign up to set email alerts
|

The Trans-Sutural Distraction Osteogenesis for 22 Cases of Craniosynostosis: A New, Easy, Safe, and Efficient Method in Craniosynostosis Surgery

Abstract: Background: Distraction osteogenesis for the treatment of craniosynostosis is becoming more widely used as it is simple, there are less transfusions, and a decreased incidence of complications, although a secondary procedure for the removal of the distractors is necessary. However, to date all previous procedures have still been complicated. The authors present a novel trans-sutural distraction osteogenesis method (TSuDO) for the treatment of all types of craniosynostosis. Methods: The TSuDO consisted of simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 67 publications
3
19
1
Order By: Relevance
“…9,12,22 The male to female ratio showed a higher proportion of females with bicoronal and unilateral coronal craniosynostosis, which is similar to results in past studies. 12 Our patients with secondary craniosynostosis had lower mean gestational ages and mean birth weights, which we presume is a natural phenomenon due to overall brain and systemic underdevelopment.…”
Section: Results Of the Tsdo Operative Technique In 285 Children Withsupporting
confidence: 89%
See 4 more Smart Citations
“…9,12,22 The male to female ratio showed a higher proportion of females with bicoronal and unilateral coronal craniosynostosis, which is similar to results in past studies. 12 Our patients with secondary craniosynostosis had lower mean gestational ages and mean birth weights, which we presume is a natural phenomenon due to overall brain and systemic underdevelopment.…”
Section: Results Of the Tsdo Operative Technique In 285 Children Withsupporting
confidence: 89%
“…LP pressure was shown to be particularly lower in children with secondary craniosynostosis after surgery. 21,22 In the present study, the subgroup of patients with LP pressures less than 20 cmH 2 O demonstrated no significant difference in operative time but significantly less mean total transfusion volume (p < 0.05) compared with those with greater than 20 cmH 2 O of LP pressure. We believe the reason for this difference in total transfusion volume is due to the increased volume of drainage via the extracranial pathway, which results from increased ICP, so that greater blood loss occurs when incising the scalp and removing the fused skull suture.…”
Section: Perioperative Lp Pressure and Head Sizecontrasting
confidence: 43%
See 3 more Smart Citations